Spatio-temporal compliance monitoring in land administration using an earth observation-enabled LADM framework - Yilmaz, Okan; Alkan, Mehmet (ELSEVIER, 2026)
Land Administration Systems (LAS) have traditionally been designed as systems where legal records are updated through formal transactions, yet physical reality monitoring remains largely reactive. While these systems effectively record legal rights (tenure), land use restrictions (planning), and development rights (permits), the physical reality of the world is inherently dynamic. Consequently, the monitoring of conformity between de facto changes on the land (e.g., unauthorized construction, land use discrepancies) and the legal functions defined within LAS must evolve to keep pace with this dynamism. In rapidly developing nations such as T & uuml;rkiye, verifying the compliance of physical development with spatial plans necessitates continuous spatio-tempoaral monitoring. This necessity also extends to the detection of cadastral boundary encroachments. While the archive of the earth surface provided by aerial photography and satellite imagery enables the 2D and 3D comparison of legal and physical status, the temporal archival of these records serves the 4th dimension of land administration. This study aims to design the LADM Country Profile for T & uuml;rkiye regarding land administration functions and to facilitate the compliance checking of legal-physical status using remote sensing data. The functionality of the proposed model was tested at the instance level using temporal satellite imagery derived from Google Earth Engine (GEE). The results obtained from various case studies demonstrate that the proposed T & uuml;rkiye Country Profile offers comprehensive solutions for sustainable land-use governance.
Keywords: Spatio-temporal monitoring; LADM edition II; Urban dynamics; Legal status audit; Data modelling; Google earth engine (GEE); Physical Geography; Remote Sensing; Imaging Science & Photographic Technology